Go the extra mile and focus on communicative competence and confidence for competitive edge, says study committee sc - Wan Jumani, Fauzi; Ruhil Amal, Azmuddin (2022)
17 February 2022 - The Centre for Modern Languages (CML) finally had a meeting with its Study Committee (SC) that had been scheduled in December 2021 along with the Industry Advisory Panel (IAP) meeting but had to be postponed due to imminent flood. This time round, the meeting was conducted virtually via Microsoft Teams.